Diagrammatic scale for assessment of anthracnose severity in feijoa fruit - Ferreira,Ana Carolina (2021)
ABSTRACT: A diagrammatic scale of anthracnose in feijoa fruit was elaborated and validated in order to standardize disease severity assessments. The proposed scale showed six disease severity levels: 2, 10, 20, 40, 70 and 100% of the injured fruit surface. The scale took into account the minimum and maximum limits of disease severity observed in the field and the intermediate values followed logarithmic increments according to the Weber-Fechner stimulus-response law. Eight inexperienced raters validated the scale by quantifying the disease severity (using/not using the scale) of 50 feijoas with anthracnose symptoms. In conclusion, the scale improved the assessment of anthracnose in feijoa. Eight genotypes from different crosses were tolerant to anthracnose.